METHOD VALIDATION OF CAPECITABINE IN API AND PHARMACEUTICAL DOSAGE FROM BY UV SPECTROPHOTOMETRIC METHOD - KAR, AYAN KUMAR; KAR, BANHISHIKHA; MAHANTI, BEDUIN; KUMAR, CHANDAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The simple, rapid spectrophotometric method was developed for the determination of capecitabine, an anticancer drug, in pharmaceutical formulations. Among the approaches, most commonly used targeted mechanism is pH-dependent delivery system which is based on pH gradient of the gastrointestinal tract (GIT) that increases progressively from the stomach. Methods: The focus of the present study is to similarize the capecitabine drug in bulk form with the marketed tablet (Capegard 500) on the simple, accurate, and precise manner by UV spectrophotometer. Results: Beer’s law was obeyed over a concentration range of 5–30 μg/mL in HCl at pH 1.2 and in phosphate buffer at pH 6.8 and 7.4. The linear regression equations of pure drug were found to be y = 0.0135x+0.2014, y = 0.0147x+0.2153, and y = 0. 0245x+0.1507 in HCl, phosphate buffer at 6.8 and 7.4, respectively, whereas the linear regression equations of marketed tablet were found to be y = 0.0158x+0.1964, y = 0.0192x+0.2261, and y = 0.015x+0.2032, respectively, and the three methods were validated as per the International Council for Harmonisation guideline (ICH). Conclusion: The regression values of every equation were found to be above 0.990 which indicated that all the equations were maintaining linearity.